Analisis Dompet Digital “Link Aja Syariah” dari Perspektif Maslahah Mursalah - Anisa Fadilah Zustika Zustika; Achmad Fageh Fageh (Faculty of Economics and Management, 2022)
Industry of 4.0 era it is no stranger to talk about digital wallets whose existence can make it easier for humans to make payment systems.There are many kinds of digital wallets in Indonesia, first one that is sharia-based is the